Sports marketing - Fullerton, Sam (McGraw-Hill/Irwin, 2007)
Sports Marketing presents this field as a new discipline, helping readers gain a stronger understanding of how to apply marketing strategies and tactics within the sports marketing environment. Fullerton crafted this new text to present the discipline of sports marketing in two broad perspectives. The first part of the text (Chapters 3 - 14) examines using a sports platform as a foundation for the marketing of non-sports products, including examples such as Tiger Woods' endorsement of Tag Heuer watches and Coca-Cola's sponsorship of soccer's World Cup.